THE IMPACT OF ORANGE JUICE ON THE SÃO PAULO ECONOMY: A CURRENT ANALYSIS: uma análise atual - Goularte Pereira, Anna Julia; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2024)
The agribusiness of São Paulo oranges is one of the most important agricultural activities, with 70% of the production going to the agroindustries to become juices (concentrated and fresh) and be marketed to the whole world. Like the other crops present in Brazil and the state, oranges have a favorable climate, fertile land and technologies for efficient planting that has been evolving over the years. The objective of this work is to contextualize the orange juice agribusiness in the State of São Paulo, through key factors such as: the historical aspects of these plants, the varieties cultivated, their production chain and their economic importance and projections. Resulting in a production chain that takes into account the demands of the domestic and foreign markets, with agro-industries as the main link. Its economic importance is based on productivity of 35.2 tons/hectare in São Paulo, 3 million tons of juices exported, employing more than 200,000 people, acquisition of work materials, life insurance and collection of US$ 189 million, with a GDP of US$ 6.5 billion and an export of US$ billion in exports per year. As final considerations, the objective was achieved, as the orange juice production chain and its economic importance were presented throughout the work, according to what was proposed.
Keywords: Agribusiness; Citrus Production; Commercialization; Agricultural Production